130k views
0 votes
Please help me out

The equation 9(w + 7) = 27 solved in several steps below.
For each step, choose the reason that best justifies it.
The options are the same for each one.

Please help me out The equation 9(w + 7) = 27 solved in several steps below. For each-example-1
Please help me out The equation 9(w + 7) = 27 solved in several steps below. For each-example-1
Please help me out The equation 9(w + 7) = 27 solved in several steps below. For each-example-2
User Bek Raupov
by
5.4k points

1 Answer

1 vote

For this case we have the following equation:


9 (w + 7) = 27

To solve we follow the steps below:

We apply Distributive Property to the terms of parentheses:


9w + 63 = 27

We apply Subtraction Property of equality by subtracting 63 from both sides of the equation:


9w + 63-63 = 27-63\\9w = -36

We apply Division Property of equality by dividing by 9 on both sides of the equation:


\frac {9w} {9} = \frac {-36} {9}

simplifiying

w = -4

Answer:


w = -4

User Irfan TahirKheli
by
6.2k points